2016
DOI: 10.3748/wjg.v22.i8.2512
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 analogue prevents nonalcoholic steatohepatitis in non-obese mice

Abstract: These results suggest that GLP-1 inhibits hepatic steatosis and inflammation through the inhibition of hepatic FFA influx and oxidative stress in a non-obese NASH model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 31 publications
2
26
0
1
Order By: Relevance
“…In vitro and in vivo studies have suggested that GLP-1RAs induce hepatic gene expression of pathways that improve autophagy/ endoplasmic reticulum stress, macrophage recruitment, and enhance mitochondrial function and hepatocyte fatty acid oxidation, resulting in a decrease in steatosis and inflammation. [100][101][102][103][104][105][106][107] However, their mechanism of action in humans is less clear. GLP-1RAs induce weight loss, 108 although there are clear differences in their potency, with minimal weight loss with albiglutide in contrast to the significant weight loss of about 10% observed with semaglutide.…”
Section: Lactate Amino Acidsmentioning
confidence: 99%
“…In vitro and in vivo studies have suggested that GLP-1RAs induce hepatic gene expression of pathways that improve autophagy/ endoplasmic reticulum stress, macrophage recruitment, and enhance mitochondrial function and hepatocyte fatty acid oxidation, resulting in a decrease in steatosis and inflammation. [100][101][102][103][104][105][106][107] However, their mechanism of action in humans is less clear. GLP-1RAs induce weight loss, 108 although there are clear differences in their potency, with minimal weight loss with albiglutide in contrast to the significant weight loss of about 10% observed with semaglutide.…”
Section: Lactate Amino Acidsmentioning
confidence: 99%
“…Further exploration has shown that DKS26 stimulates hepatic AMPK phosphorylation in vitro (data not shown). As an enhanced sensitivity of hepatic insulin contributes to decreased hepatic lipid accumulation (Hwang et al, ), and a GLP‐1 receptor agonist ameliorates steatohepatitis (Wang et al, ; Yamamoto et al, ), we speculate that the hepatoprotection of DKS26 mediated by its effects on AMPK might be as a consequence of it directly or indirectly improving insulin sensitivity or activating the GLP‐1 receptor to alleviate hepatic fat accumulation and inflammation, but this remains to be further confirmed.…”
Section: Discussionmentioning
confidence: 75%
“…This is a significant advantage over TZDs, which have the side effect of weight gain. Furthermore, GLP‐1RAs ameliorate insulin resistance and lipotoxicity, and both GLP‐1RAs and DPP‐4 inhibitors have been reported to exert anti‐steatotic and anti‐inflammatory effects . As GPR119 ligands stimulate GLP‐1 release and increase glucose‐dependent insulin secretion, they may also be promising therapeutic options.…”
Section: Pharmacological Applications Of Gpr119 Ligandsmentioning
confidence: 99%
“…Furthermore, GLP-1RAs ameliorate insulin resistance and lipotoxicity, and both GLP-1RAs and DPP-4 inhibitors have been reported to exert antisteatotic and anti-inflammatory effects. [96][97][98][99][100][101] As GPR119 ligands stimulate GLP-1 release and increase glucose-dependent insulin secretion, they may also be promising therapeutic options. Indeed, our group recently reported that the GPR119 agonists MBX-2982 and GSK1292263 inhibited hepatic lipogenesis and thereby prevented hepatic steatosis.…”
Section: Anti-diabetesmentioning
confidence: 99%